The polLux microspectroscopy beam line at the swiss light source - Fink, Rainer; Raabe, Jörg; Quitmann, Christoph; Ade, Harald; et al. (SYNCHROTRON RADIATION INSTRUMENTATION, 2007)
The optical design and performance expectations of a Fresnel zone plate based scanning transmission x-ray microscopy (STXM) beamline at a bending magnet of the Swiss Light Source is described. The instrument allows microspectroscopy in polymer science in the water window and the study of magnetic materials with circularly polarized light. The beamline is based on a spherical grating monochromator with two gratings at a constant deviation angle and covers a photon energy range from 200 eV to 1000 eV. © 2007 American Institute of Physics.